The biocontrol strain Bacillus mojavensis KRS009 confers resistance to cotton Verticillium wilt and improves tolerance to salt stress - Zhao, Fuhua; Wang, Dan; Liu, Huizi; Shan, Yujia; Qi, Hong‐Yue; Dai, Xiaofeng; Chen, Jieyin; Lesueur, Didier; Han, Dongfei; Zhang, Xiaojun; Zhang, Dandan (Wiley, 2024)
Abstract Biological control has gained increasing attention as a strategy to address biotic and abiotic stresses in crops. In this study, we identified the strain KRS009 as Bacillus mojavensis through morphological identification and multilocus sequence analysis. KRS009 exhibited broad‐spectrum antifungal activity against various phytopathogenic fungi by secreting soluble and volatile compounds. Additionally, the physio‐biochemical traits of strain KRS009 were characterized, including its growth‐promoting capabilities and active enzymes. Notably, KRS009 demonstrated the capacity for biofilm formation and exhibited tolerance to saline‐alkali conditions. The biological security evaluation confirmed the safety of KRS009 for both humans and plants. Furthermore, strain KRS009 was found to trigger plant immunity by inducing systemic resistance through salicylic acid‐ and jasmonic acid‐dependent signaling pathways. Greenhouse experiments conducted on cotton plants proved that the treatment with strain KRS009 effectively protected cotton against Verticillium wilt caused by Verticillium dahliae and promoted the growth of cotton under salt stress. These findings highlight the potential of B. mojavensis KRS009 as a promising biocontrol and biofertilizer agent for promoting plant growth, combating fungal diseases and mitigating salt stress in plants.